QUORUM SENSING ANALYSIS AND EFFECT OF BACTERIOCIN IN CONTROLLING THE BIOFILM FORMATION OF PSEUDOMONAS AERUGINOSA - DHARSINI, S. PRIYA; BHUVANESHWARI, G.; KALYANI, M.; VENILLA, ROSY (International Journal of Current Pharmaceutical Research, 2020)
Objective: Pseudomonas aeruginosa is the commonest causative agent of Hospital Acquired Infection (HAI). Resistance of Pseudomonas aeruginosa towards disinfectants and antibiotics is high when compared to other organisms. There are various reviews on antibacterial effect of herbal extracts and nanoparticles against Pseudomonas aeruginosa. Thus, this study aims to prove the effectiveness of bacteriocin against Pseudomonas aeruginosa, which may help in benefiting the health care center by replacing normal disinfectants. Methods: 100 strains of Pseudomonas aeruginosa were collected from different patients, with a study period of 6 mo. Ammonium sulfate precipitation method was used to extract bacteriocin and its efficiency was checked by paper disc diffusion assay. Biofilm formation assay and quorum sensing analysis was performed by Microtitre plate methods and Thin Layer Chromatography (TLC), respectively. Results: In this study, 91%of P. aeruginosa strains were strong, 8% were intermediate, and 1% were weak biofilm producers. From TLC analysis, 67% of the strains produced Acyl Homoserine Lactone molecules. Out of which, 49% has shown unknown analytes of Retardation factor (Rf) value greater than 1. The Rf values identified were 3 unsubstitutedC4 (5%), 3 unsubstituted C6 (4%), 3 oxo C8 (3%), 3 oxo C4 (3%), 3 oxo C6 (2%), 3 oxo C1 (1%). Biofilm production, before and after bacteriocin exposure, was proved significant by paired t-test. Conclusion: Quorum sensing was confirmed to play a major role in biofilm formation. As bacteriocin was found to be effective in controlling the biofilm formation, it can be incorporated in any disinfectant, which helps in controlling the transmission of infection caused by Pseudomonas aeruginosa.